Evaluación de rendimiento de híbridos simples y triples de maíz blanco (Zea mays) en el valle del río carrizal - Moreira Cedeño, Wilder Bismark (2025)
Maize is a crop of great economic and food importance worldwide, serving as a key source of sustenance for millions of people. The present research, conducted in the conventional area of the Agricultural Engineering program at ESPAM MFL, aimed to evaluate the performance of single and triple white maize hybrids in the Carrizal River Valley. Twelve single hybrids, one triple hybrid, and two commercial controls were evaluated, establishing 15 treatments with three replications and a total of 45 experimental units. The experimental variables considered included days to female and male flowering, plant height, ear height, root and stalk lodging, ear rot, ear appearance, moisture percentage, shelling, and grain yield at 13% moisture. Agronomic and phytosanitary variables were significantly affected (p < 0.05) by the evaluated hybrids. The variety INIAP-543QPM and the single hybrids INIAP-543QPM/CML-498 and CML-494/INIAP-543QPM were the earliest to flower (both male and female). Additionally, disease incidence caused by Bipolaris, Puccinia, and Red Stripe was low in these hybrids. Economically, T15 INIAP-543QPM presented the lowest net benefit, generating the lowest profitability among all evaluated hybrids, compared to T12 CLRCW97/CML494, which achieved higher economic profitability per hectare. Under the conditions where the experiment was conducted, the hybrid T12 CLRCW97/CML494 appears as a viable genetic material for maize production in the Carrizal River Valley.